Impact of Hotel Employees’ Mental Health During Pandemic on The Level Of Quality Service - Harvey Cabarrubias Cabarrubias; Nhel Dela Cruz; Trisha Janelle Lazo; Patrick Mapande; Berlyn Sumaoang (Logistic and Operation Management Research (LOMR), 2022)
Despite the continued outbreak of the new COVID-19, few studies on the stress associated with the pandemic have been done. In this study, attributes of mental health perceived by hotel employees and hotel customers were examined, and the service quality, in terms of reliability, responsiveness, assurance, empathy, and tangibles. We found and verified attributes based on qualitative approaches. As a result, it was found that the relationships between the proposed variables had no significant effects. This study provides an evaluation of the impact of mental health on hotel employees' performance and the level of service they deliver.